The Intercalation of Copper into Active Carbon and Its Application as a Catalyst for n-Amylalcohol Dehydration - Rusman Rusman; Iip Izul Falah; RHA. Sahirul Alim (Indonesian Journal of Chemistry, 2001)
The intercalation of CuCl2 salts into active carbon and its activity as catalyst on dehydration of n-amylalcohol has been investigated. In this research, the intercalation was conducted by reacting CuCl2 powder with active carbon and Cl2 gas at 3 atm, temperature 575 °C, at various heating time. This process was then followed by the reduction in the flowing hydrogen gas. Characterization of intercalation product was conducted by gas sorption method to determine surface area, pore radius, and pore volume distribution, and atomic adsorption spectroscopy (AAS) was used to determine the content of Cu metal. The test of catalytic activity on dehydration reaction of n-amylalcohol, was carried out in a flow reactor system at various temperatures. The results showed that the surface area and total pore volume increase with the longer time of intercalation process, and followed by increasing Cu content on active carbon. It was showed further that catalyst with highest Cu content, and the largest of both of surface area and total pore volume gives the best performance.